2009
DOI: 10.2136/sssaj2008.0267
|View full text |Cite
|
Sign up to set email alerts
|

Soil Metals Analysis Using Laser‐Induced Breakdown Spectroscopy (LIBS)

Abstract: Laser‐induced breakdown spectroscopy (LIBS) is an elemental analysis technique that is based on the measurement of atomic emissions generated on a sample surface by a laser‐induced microplasma. Although often recognized in the literature as a well‐established analytical technique, LIBS remains untested relative to the quantitative analysis of elements in chemically complex matrices, such as soils. The objective of this study was to evaluate the capabilities of LIBS relative to the elemental characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…LIBS is a well-established atomic-emission technique extensively applied for surface analyses in research and industry (Balzer et al, 2005;Essington et al, 2009;Merdes et al, 2007). It involves focusing a pulsed laser-beam ~50 μm diameter on a sample and ablating a small amount, ~10 -9 cm 3 , of the material (Martin et al, 2010).…”
Section: Libsmentioning
confidence: 99%
“…LIBS is a well-established atomic-emission technique extensively applied for surface analyses in research and industry (Balzer et al, 2005;Essington et al, 2009;Merdes et al, 2007). It involves focusing a pulsed laser-beam ~50 μm diameter on a sample and ablating a small amount, ~10 -9 cm 3 , of the material (Martin et al, 2010).…”
Section: Libsmentioning
confidence: 99%
“…Al, Si) and some other with a very high number of spectral lines (e.g. Fe, Ti, Mn, Ca) rising up the risk of spectral interference [12]. Consequently, quantitative LIBS remains very challenging and specific studies should be conducted either to take into account the matrix effect through advanced data processing in the case of the approach with calibration or to discuss the condi tions of stoichiometry for applying the calibration free algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Sirven et al [15] used partial least square regression (PLS) to quantify chromium in artificially prepared soil samples and obtained a good improvement of prediction of concen trations compared to univariate calibration method. But at the opposite, Essington et al [12] applied PLS to LIBS and ICP AES data from natural soils originating from East Tennessee and obtained relative errors of prediction not smaller than the one provided by univariate approach. They also noticed that the analytically viable methods of analysis are de fined by an average relative error of prediction below 20%.…”
Section: Introductionmentioning
confidence: 99%
“…A method that is fast, accurate, and cost effective is needed for estimating heavy metal concentration in soils. Conventional atomic spectroscopic techniques have acceptable analytical performance, but their sample preparation is time consuming and requires the use of hazardous chemicals (Hussain et al, 2007;Essington et al, 2009). Laser-induced breakdown spectroscopy (LIBS) is a fast total-elemental analytical technique that has potential advantages over the conventional analytical techniques because of a simple and compact experimental setup, less sample preparation, less destructive, and can be used in remote in-situ analysis in hostile environments and hazardous or inaccessible targets (Miziolek et al, 2006;Hussain et al, 2007;Martin et al, 2010).…”
mentioning
confidence: 99%
“…However, for spectra obtained from soil samples, the previous method is not practical because soil is a chemically complex matrix containing a host of other elements. Essington et al (2009) reported that soil spectra were dominated by peaks of Al, Ca, Mg, and Fe, and some of which had more than a hundred peaks. The existence of these soil elements can interfere and overshadow most of the trace elements that might be of interest and make it hard to identify all the useful peaks for the specific element.…”
mentioning
confidence: 99%